Pertunjukan Solis Marimba dan Drumset Dengan Repertoar Concerto In B Minor Zapin Kerinduan dan Naruto Main Theme (Jurnal Sitakara, 2023)
This solo marimba and drumset performance presented 3 repertoires namely Concerto In B Minor, Zapin Longing, and Naruto Main Theme. The first repertoire of the Concerto in B Minor is a romantic work by O. Rieding.. This work is a three-part work with the tempo Allegro moderato, Andante and Allegro moderato. The next repertoire is the Malay repertoire, namely, Zapin Longing.  the director and composer of this music group is Rino Dezapati. The last repertoire is Naruto Main Theme. which was created by Yasuhara Takanasi In 2008.Keywords:  Show, Repertoire,  percussion.